Uma abordagem para obtenção de regiões ortólogas em múltiplos proteomas - Silva, Anderson Pegoraro (2016)
With the progress of the sequencing techniques and the inevitable increasing number of sequenced genomes, it becomes interesting studying computational techniques to analyze these data. One of the possible analyses refers to the extraction of functional and evolutionary characteristics of the studied organisms. Thus, in this line of research, this study is motivated in identifying common regions, in terms of the genes that they contain, in multiple proteomes that keep the order and the gene content. The problem is modeled with a colored graph, and the common regions between proteomes are like clicks in the graph. Using peculiarities of the constructed graph, an algorithm for search space reduction was developed, making it possible to get complete results in a short time. Therefore, the contribution of this work constitutes an approach to find common regions in multiple proteomes, added of an implementation from which the Multiple Proteome Comparison (MPC) tool originated.